Upstream open reading frame translation enhances immunogenic peptide presentation in mitotically arrested cancer cells - Kowar, Alexander; Becker, Jonas Philipp; Pizzo, Rossella del; Tang, Zhiwei; Champagne, Julien; Wellach, Kathrin; Samimi, Kiana; Galindo-Albarrán, Ariel; Körner, Pierre-René; Montenegro Navarro, Jasmine; Elía, Andrés; Tilghman, Fiona Megan; et al. (Nature Communications, 2025)
Mitosis is a critical phase of the cell cycle and a vulnerable point where cancer cells can be disrupted, causing cell death and inhibiting tumor growth. Challenges such as drug resistance persist in clinical applications. During mitosis, mRNA translation is generally downregulated, while non-canonical translation of specific transcripts continues. Here, we show that mitotic cancer cells redistribute ribosomes toward the 5′ untranslated region (5′ UTR) and beginning of the coding sequence (CDS), enhancing translation of thousands of upstream open reading frames (uORFs) and upstream overlapping open reading frames (uoORFs). This mitotic induction of uORF/uoORF enriches human leukocyte antigen (HLA) presentation of non-canonical peptides on the surface of cancer cells after mitotic inhibitor treatment. Functional assays indicate these epitopes provoke cancer-cell killing by T cells. Our findings highlight the therapeutic potential of targeting uORF/uoORF-derived epitopes with mitotic inhibitors to enhance immune recognition and tumor cell elimination.